(untitled) (Nepalese Journal of Radiology, 2023)
Introduction:Sclerotherapy, a minimally invasive approach, has gained prominence as a therapeutic modality for the treatment of these lesions. The objective of this article is to assess clinical success, complications and periprocedural pain score of sclerotherapy and their variation with the nature of the lesion and choice of sclerosants. Methods: This was a hospital record-based retrospective study in a tertiary care centre in Kathmandu. Sclerotherapy done in the institute from January 2019 to December 2022 was evaluated for the nature of the lesion, clinical success, number of sessions, periprocedural pain score and complications. All sclerotherapy was performed under combined USG and fluoroscopic guidance by an interventional radiologist. Data was entered in predesigned proforma and data analysis was done using SPSS 25.0. Results: A total of 33 patients underwent 61 sessions of sclerotherapy during the study period. Venous malformation (72.2%) was the most common vascular lesion followed by hemangioma. There was significant resolution of symptoms post sclerotherapy pain relief in 95% complete resolution of swelling in 65.38 % and partial resolution with acceptable cosmetic results in 26.92% of cases. Only minor complications were seen in 6.5% of cases. The median periprocedural pain score was 5 with an interquartile range of 2. Periprocedural pain was significantly less with sodium tetradecyl sulphate than with alcohol(P-0.002). The resolution of swelling was less in hemangiomas than in other lesions, while pain relief was similar for all lesions. Complications were seen only in the alcohol group. Conclusions: Sclerotherapy is a safe and effective procedure for benign vascular lesions. Complications and periprocedural pain are less with sodium tetradecyl sulphate as compared to alcohol.